Early Heidegger's Methodology and Its Challenges for the Future - Klun, Branko (Toronto journal of theology, 2014)
This paper analyzes the phenomenological method in Heidegger's early Freiburg lectures, which distinguishes three dimensions of sense for a phenomenon (content, relation, and actualization sense). Through a specific phenomenological reduction to the original Vollzugssinn (actualization sense) of a phenomenon within concrete factical life, Heidegger literally breathes new life into static phenomena within the non-temporal, theoretical approach. However, the enormous potential in analyzing phenomena within the horizon of temporality and historicity also sets some methodological limits that still represent a challenge for the future development of hermeneutic phenomenology, especially in its dialogue—which will be considered only briefly in this article—with two important areas: theology and science.